2021
DOI: 10.1177/10242589211031103
|View full text |Cite
|
Sign up to set email alerts
|

Applauded ‘nightingales’ voicing discontent. Exploring labour unrest in health and social care in Europe before and since the COVID-19 pandemic

Abstract: News and BackgroundApplauded 'nightingales' voicing discontent. Exploring labour unrest in health and social care in Europe before and since the COVID-19 pandemic 1 Reference is made to health and social care throughout this article, as official statistical data on industrial action cover both. It is, however, acknowledged that different care occupations have distinctive histories of labour unrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Trade unions have fought alongside platform workers and won important court cases to have platform workers reclassified as employees so that platform enterprises assume responsibility for the protections afforded to these workers by labour law (Vandaele 2018). In December 2021, the Supreme Court in India agreed to hear a petition filed by one union representing 20,000 home delivery workers, which called for social security benefits to be extended to workers of app-based platforms (Chaturvedi 2021).…”
Section: Employers' Organizations and Trade Unions: Restructuring And...mentioning
confidence: 99%
“…Trade unions have fought alongside platform workers and won important court cases to have platform workers reclassified as employees so that platform enterprises assume responsibility for the protections afforded to these workers by labour law (Vandaele 2018). In December 2021, the Supreme Court in India agreed to hear a petition filed by one union representing 20,000 home delivery workers, which called for social security benefits to be extended to workers of app-based platforms (Chaturvedi 2021).…”
Section: Employers' Organizations and Trade Unions: Restructuring And...mentioning
confidence: 99%
“…Protecting them became a top priority for governments in the different waves experienced during 2020. However, this was not always free from tensions (Vandaele 2021). In all countries, claims were made regarding understaffing, resulting from the implementation of cuts in public health systems during or following the Great Recession that had not been fully overcome.…”
Section: Healthcare Workersmentioning
confidence: 99%
“…While various scholars have long highlighted the important role of the state and the public sector in industrial relations (Howell, 2009;Meardi, 2014;Meardi et al, 2016), the outburst of the COVID-19 pandemic re-confirmed the importance of the stateand of public employeesin the provision of public goods and services to the community. Thus, growing societal support for the prolonged public employees' struggles has contributed to partially reverse the post-crisis trend, favouring the improvement of public sector employment and pay conditions, especially in the healthcare sector (Vandaele, 2021).…”
Section: Introductionmentioning
confidence: 99%